113. Impact of Urinalysis with Reflex to Culture on Antimicrobial Prescribing Patterns for Patients with a Positive Urine Culture. (31st December 2020) - Diehl, Nicolette; Yu, Daohai; Gallagher, Jason C; Sullivan, Kaede V; Mueller, Daniel; Lu, Xiaoning; Cavaretta, Marissa
Abstract: Background: Temple University Hospital recently implemented a protocol in which a urinalysis will reflex to culture only in the presence of pyuria. The purpose of this study is to compare appropriate antimicrobial use for patients with positive urine cultures before and after implementation of the urinalysis with reflex to culture protocol. Methods: This is a single center, observational chart review. Adult internal medicine patients with a urinalysis and positive urine culture before and after the intervention were included in the pre- and post-intervention groups. Patients in the intensive care unit, undergoing urologic or surgical procedures, with leukopenia, being treated for another infection, who were discharged within 72 hours of the urine culture order, or pregnant were excluded. The primary endpoint was the percentage of patients with appropriate antimicrobial management of the positive urine culture before and after implementation of the protocol. Appropriate management was defined as antimicrobial treatment for a symptomatic urinary tract infection or no antimicrobial treatment for asymptomatic bacteriuria. Duration of therapy was also assessed. A sample size of 334 cultures was needed to detect a 15% difference in initiation of antibiotics between groups. Comparisons of categorical variables were analyzed by Chi-Square/Fisher exact test while continuous variables were analyzed by Wilcoxon test. Results: Patient characteristics and outcomes are listed in the tables below. Table 1: Patient Characteristics Table 2: Outcomes Conclusion: The urinalysis with reflex to culture intervention appeared to have minimal impact on the management of patients with a positive urine culture, with a possible increase in inappropriate management. Duration of therapy was significantly reduced by approximately one day with the intervention. Additional interventions to improve appropriate management of bacteriuria should be explored. Disclosures: Jason C. Gallagher, PharmD, FIDP, FCCP, FIDSA, BCPS, Allergan (Consultant)Astellas (Consultant)Merck (Consultant, Grant/Research Support)Nabriva (Consultant)Qpex (Consultant)scPharmaceuticals (Consultant)Shionogi (Consultant)Spero (Consultant)Tetraphase (Consultant)